AAV- based vector improvements unrelated to capsid protein modification - Shitik, Ekaterina M.; Shalik, Igor K.; Yudkin, Dmitry V. (Frontiers in Medicine, 2023)
Recombinant adeno-associated virus (rAAV) is the leading platform for delivering genetic constructs in vivo. To date, three AAV-based gene therapeutic agents have been approved by the FDA and are used in clinical practice. Despite the distinct advantages of gene therapy development, it is clear that AAV vectors need to be improved. Enhancements in viral vectors are mainly associated with capsid protein modifications. However, there are other structures that significantly affect the AAV life cycle and transduction. The Rep proteins, in combination with inverted terminal repeats, determine viral genome replication, encapsidation, etc. Moreover, transgene cassette expression in recombinant variants is directly related to AAV production and transduction efficiency. This review discusses the ways to improve AAV vectors by modifying inverted terminal repeats, a transgene cassette, and the Rep proteins.